Autopoiesis, creativity and dance. Issue 1 (2nd January 2017) - Bishop, J. Mark; al-Rifaie, Mohammad M.
ABSTRACT: For many years three key aspects of creative processes have been glossed over by theorists eager to avoid the mystery of consciousness and instead embrace an implicitly more formal, computational vision: autonomy, phenomenality and the temporally embedded and bounded nature of creative processes. In this paper we will discuss autopoiesis and creativity; an alternative metaphor which we suggest offers new insight into these long overlooked aspects of the creative processes in humans and the machine, and examine the metaphor in the context of dance choreography.